Pharmaceutical and Medical Device Resilience: Implementation of Emergency Use Authorization in Pharmaceuticals and Medical Devices During the Covid-19 Pandemic: a Literature Review - Nurul Safitri; Dumilah Ayuningtyas (International Journal Labs, 2023)
The COVID-19 pandemic has caused an urgent need for pharmaceuticals and medical devices used for testing, treatment, and prevention. The policy of issuing an Emergency Use Authorization (EUA) for COVID-19 handling products is carried out to fulfill these needs. This study aims to describe and analyze how the EUA mechanism can be used as resilience during the pandemic. The study used Pubmed and ScienceDirect databases to search all articles using inclusion and exclusion criteria. The inclusion criteria were articles in English and Indonesian, national and international research articles covering the application of the EUA, searches limited to the last 3 years, and articles not limited to one study design. The exclusion criteria were articles not available in full text and topics unrelated to EUA in pharmaceuticals and medical devices. A total of 1,009 articles were identified using the keywords “Emergency Use Authorization”, “drug or medical device”, “COVID-19”. Finally, 11 articles that met the criteria were analyzed. The EUA approval for pharmaceuticals and medical devices is a form of resilience in the face of a pandemic and is an effective way to meet increasing needs while looking at clinical evidence and evidence of use in the field. The ability and experience in implementing the EUA can be a guide for learning in dealing with pandemics in the future.